The Genome of Staphylococcus epidermidis O47 - Raue, Stefan; Fan, Sook-Ha; Rosenstein, Ralf; Zabel, Susanne; Luqman, Arif; Nieselt, Kay; Götz, Friedrich (Frontiers in Microbiology, 2020)
The skin colonizing coagulase-negative Staphylococcus epidermidis causes nosocomial infections and is an important opportunistic and highly adaptable pathogen. To gain more insight into this species, we sequenced the genome of the biofilm positive, methicillin susceptible S. epidermidis O47 strain (hereafter O47). This strain belongs to the most frequently isolated sequence type 2. In comparison to the RP62A strain, O47 can be transformed, which makes it a preferred strain for molecular studies. S. epidermidis O47's genome has a single chromosome of about 2.5 million base pairs and no plasmid. Its oriC sequence has the same directionality as S. epidermidis RP62A, S. carnosus, S. haemolyticus, S. saprophyticus and is inverted in comparison to Staphylococcus aureus and S. epidermidis ATCC 12228. A phylogenetic analysis based on all S. epidermidis genomes currently available at GenBank revealed that O47 is closest related to DAR1907. The genome of O47 contains genes for the typical global regulatory systems known in staphylococci. In addition, it contains most of the genes encoding for the typical virulence factors for S. epidermidis but not for S. aureus with the exception of a putative hemolysin III. O47 has the typical S. epidermidis genetic islands and several mobile genetic elements, which include staphylococcal cassette chromosome (SCC) of about 54 kb length and two prophages φO47A and φO47B. However, its genome has no transposons and the smallest number of insertion sequence (IS) elements compared to the other known S. epidermidis genomes. By sequencing and analyzing the genome of O47, we provide the basis for its utilization in genetic and molecular studies of biofilm formation.